(untitled) (Journal of the College of Basic Education, 2023)
The current research aims to identify the effectiveness of a counseling program in development Interactive Care among educational counselors by testing the hypothesis that ((there are no statistically significant differences between the scores of the two experimental and control groups on the scale of Interactive Care in the pre and post tests and deferred at the level of significance 0.05)). For the purpose of identifying the level of Interactive Care of the sample, the researcher adopted a scale (Noory, 2016), then the researcher extracted the statistical characteristics of the scale and it was found that all situations have discrimination and a statistically significant correlation. As the correlation coefficient for the stability of the scale was (0.84), and the value of Cronbach’s alpha was (0.79), and the items of the scale were (40) items with three responses. After applying the counseling program to the experimental sample, the results of the current research concluded that there are statistically significant differences between the experimental and control groups in the post-test and in favor of the experimental one. The findings of the current research are stable, and in the light of these results, the researcher presented a number of conclusions, recommendations and suggestions.